Aktivitas Elo Pukek Di Pesisir Selatan Dalam Seni Lukis Realis - Yofri Hardiansah; Yasrul Sami (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
The purpose of this final work is to visualize the elo pukek activity in South Pesisir in realist painting. This is a form of the author's anxiety towards fishermen who participate in elo pukek activities who have less income in proportion to the hard work and risks faced, such as erratic waves, changing weather and sea animals that suddenly attack. The method of creation in the final work is carried out in stages, namely the preparation stage by searching for information, elaboration by analyzing the problem, synthesis setting the idea, realization of the concept by making realist paintings and the completion stage by conducting an exhibition. Ten paintings with a size of 100 cm x 100 cm with acrylic media on canvas based on the theme of "social phenomena" in accordance with the predetermined idea of elo pukek activities by South Pesisir fishermen were developed through ten work titles namely "starting", "hope", "compactness", "spirit", "tough", "unwinding", "results", "buying", "carefree", "sweat".